Prevalence and temporal trends in myopia and high myopia children in China: a systematic review and meta-analysis with projections from 2020 to 2050Research in context - Wei Pan; Seang-Mei Saw; Tien Yin Wong; Ian Morgan; Zhikuan Yang; Weizhong Lan (The Lancet Regional Health. Western Pacific)
Summary: Background: Myopia rates have risen in the past decades in China. New strategies for the prevention and control of myopia are now available, and understanding the prevalence and future trends in myopia and high myopia in children and adolescents in China may provide insights into the impact of implementing these measures. The study aims to provide updated data on the prevalence of myopia and high myopia in children and to project temporal trends in prevalence from 2020 to 2050 in China. Methods: A systematic review and meta-analysis searching several databases in both English and Chinese: PubMed, Web of Science, Science Direct, China National Knowledge Infrastructure (CNKI), Wanfang, China Science and Technology Journal Database (CSTJ) with date limits from 01/01/2010 to 11/23/2024 was conducted. We included population-based or school-based studies in China that determined the myopia prevalence, based on the cycloplegic refraction, in children under 20. Studies with a response rate <70% or sample size <200 were excluded. A fixed-effect meta-analysis was used, and projections were made based on three scenarios: experience-based, maximum growth (maximum near-work, minimal outdoor time), and minimum growth (2 h outdoor time daily). Findings: From 6555 reports, 82 studies with 218,794 participants were included. The overall myopia prevalence was 36.6% (95% CI: 36.4%, 36.8%), with rates of 2.6% in ages 0–4, 22.0% in ages 5–9, 45.4% in ages 10–14, and 67.2% in ages 15–19. High myopia prevalence was 5.3% overall, with rates of 0.1% in ages 0–4, 1.1% in ages 5–9, 3.0% in ages 10–14, and 9.5% in ages 15–19. Projections for 2030 under minimum growth, experience-based, and maximum growth scenarios were 26.8%, 46.2%, 56.0%; 2040 were 19.6%, 54.4%, 65.6%; and 2050 were 14.4%, 61.3%, 71.9%, respectively. Interpretation: China is facing a substantial and potentially worsening epidemic of childhood myopia. This information will provide data for guiding implementation and evaluating the effectiveness of existing and new nationwide myopia prevention and control programs. Funding: The Science and Technology Innovation Program of Hunan Province, China (2023RC1079, 2024RC5002).